Comparative analysis of work of centrifugal and by volume pumps - V. V. Kulikov (Известия высших учебных заведений: Геология и разведка, 2015)
While transporting the fluid by the pump with constant volumetric supply, the reciprocal effect of pressure loss at different parts of hydraulic line is absent. While transporting the fluid by centrifugal pump, changing of geometrical resistance (contraction, expansion, rotation of the line) at any part of the fluid moving causes the losses of pressure at every part and in the line in whole. Volumetric productivity of centrifugal pump can be calculated by equating of analytic expression of hydraulic characteristic of the pump as the equalization of quadratic regression, and equalization, describing hydraulic description of the network.